Implementation of Contextual Learning Strategies in Islamic Religious Education Subjects at Madrasah Aliyah Allu - Nurahdillah Morra Bilu; Usman U; Besse Marjani Alwi (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to examine the implementation of Contextual Teaching and Learning (CTL) in Islamic Religious Education (PAI) subjects, particularly at Madrasah Aliyah Allu. Amidst the challenges of 21st-century education that demand life skills mastery, learning practices in Indonesia are often still conventional and teacher-centered. This study uses a qualitative approach with a library research method to gather information from various scientific references. The results show that the implementation of CTL at MA Allu is carried out by integrating core components such as inquiry, questioning, learning communities, and modeling in PAI materials such as Fikih Muamalah. The application of this strategy has proven effective in increasing students' motivation, critical thinking skills, and the quality of their worship practices. However, the main challenges faced include limited time allocation, the dominance of cognitive evaluation that does not fully utilize authentic assessment, and obstacles in changing students' passive learning habits. This study concludes that institutional support, teacher training, and utilization of the surrounding environment are crucial for making PAI learning more meaningful and relevant to real life.